2004
DOI: 10.1143/jpsj.73.3331
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Fermi-Surface Nesting in 1T-VSe2Studied by Angle-Resolved Photoemission Spectroscopy

Abstract: We have performed high-resolution angle-resolved photoemission spectroscopy (ARPES) with synchrotron radiation on layered transition-metal dichalcogenide 1T-VSe 2 to study the mechanism of the three-dimensional charge-density-wave (CDW) transition. We found that the Fermi surface around the M(L) and K(H) points shows considerable wiggling along the wave vector normal to the layer (k z ) despite the apparently two-dimensional crystal structure. ARPES spectra below the CDW transition temperature show a signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
5
27
1
Order By: Relevance
“…However, tunneling spectroscopy does not show any significant reduction in the LDOS at at the phase transition ( Fig. 1b), consistent with the tiny portion of the Fermi surface that is gaped in the CDW phase of 1 -VSe 2 25 . Moreover, the vanadium derived -band just below obscures the CDW gap.…”
supporting
confidence: 65%
“…However, tunneling spectroscopy does not show any significant reduction in the LDOS at at the phase transition ( Fig. 1b), consistent with the tiny portion of the Fermi surface that is gaped in the CDW phase of 1 -VSe 2 25 . Moreover, the vanadium derived -band just below obscures the CDW gap.…”
supporting
confidence: 65%
“…We found that monolayer VSe2 shows the insulating ground state in contrast to the metallic nature of bulk. Previous ARPES studies suggested that the CDW in bulk 1T-VSe2 is triggered by the FS nesting [11,12]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 69%
“…To see more clearly the energy dispersion of the metallic V 3d band responsible for the anomalous physical properties, we show in Fig. 2 distinctly different from that of bulk VSe2 [11][12][13], suggesting that the change in the dimensionality and the resultant absence of interlayer interaction strongly influence the electronic states of monolayer VSe2.…”
Section: Resultsmentioning
confidence: 86%
“…It exhibits an incommensurate CDW with 4a × 4a × 3.18c periodic lattice distortion upon cooling to around 110 K, followed by a second transition to a commensurate CDW state at ∼ 80 K (Thompson and Silbernagel, 1979;Tsutsumi, 1982;Eaglesham et al, 1986;Terashima et al, 2003;Pandey and Soni, 2020). The mechanism of the 3D CDW was initially explained by Fermi-surface nesting resulting from the warped 3D electron pocket centered around the M point at the edge of the Brillouin zone (Terashima et al, 2003;Sato et al, 2004;Strocov et al, 2012). Recently, electron-phonon coupling was also found to contribute to the formation of the CDW (Pandey and Soni, 2020;Si et al, 2020).…”
Section: Introductionmentioning
confidence: 99%